Fabrication of WO3·2H2O/BC Hybrids by the Radiation Method for Enhanced Performance Supercapacitors - Yang, Fan; Jia, Jinzhi; Mi, Rui; Liu, Xichuan; Fu, Zhibing; Wang, Chaoyang; Liu, Xudong; Tang, Yongjian (Frontiers in Chemistry, 2018)
Herein, we described a facile process for fabrication of tungsten oxide dihydrate/bamboo charcoal hybrids (WO32H2O/BC) by the γ-irradiation method. The structural, morphological and electrochemical properties of the WO32H2O/BC hybrids had been investigated using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM), cyclic voltammetry (CV), galvanostatic charge/discharge (GCD) and electrochemical impedance spectroscopy (EIS) techniques. The combination of BC (electrical double layer charge) and WO32H2O (pseudocapacitance) created a combined effect, which enhanced the specific capacitance and good cyclic stability of the WO32H2O/BC hybrids electrode. The WO32H2O/BC hybrids showed the higher specific capacitance (391 F g–1 at a current density of 0.5 A g–1 over the potential range from –1 V to 0 V), compared with BC (108 F g–1) in 6 M KOH aqueous electrolyte. Furthermore, the WO32H2O/BC hybrids electrode showed superior cycling stability with 82% capacitance retention even after 10,000 cycles. The experimental results demonstrated that the high performance of WO32H2O/BC hybrids could be a potential electrode material for supercapacitors.